Risco Moral no Mercado de Saúde Suplementar e Efeitos da Coparticipação na Demanda por Consultas e Exames - Chaves, Arianny Mary Moura (2009)
The objective of this study is to evaluate the occurrence of moral hazard in the demand for medical and support services for diagnosis and treatment (tests) in the Brazilian supplementary health system. Specifically, we aim at the quantitative comparison of the use of health services between two types of plans: with and without coparticipação. For this, we use two methods of matching based on propensity score, where the estimators are derived from groups or strata (Stratification Matching) and from a density function (Kernel Matching). In the model of strata the estimated effect of coparticipação medical appointments was between -0.358 and -0.979 per capita per year. In the model from a kernel function, the effect of coparcenary was -0.286 to -1.031 per capita per year. In the case of examinations, the effect of coparcenary was between -2.965 and -4.652 (Stratification Matching) and -2.621 and -5.057 (Kernel Matching). In both models the Northeast had the highest effect coparcenary, both for consultations and for examinations, while the South had the smallest effect. The results achieved through the study show the occurrence of moral hazard, ie the use of health services is sensitive to the imposition of regulatory mechanisms where individuals coparticipação require medical examinations and in quantities not exceeding those without coparcenary Palavras